2001
DOI: 10.1002/1097-0142(20010715)92:2<271::aid-cncr1319>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Expression of survivin is correlated with cancer cell apoptosis and is involved in the development of human pancreatic duct cell tumors

Abstract: BACKGROUND Survivin is a new member of the inhibitor of apoptosis family of antiapoptotic proteins. This protein was expressed selectively in all the most common human carcinomas but not in normal adult tissues. To our knowledge, the relation between survivin expression and apoptosis or tumorigenesis has not yet been studied in pancreatic neoplasms. METHODS The authors investigated the expression of survivin in 4 pancreatic carcinoma cell lines and 56 human pancreatic tissues (5 cases of normal, 12 cases of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
159
1
10

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(177 citation statements)
references
References 12 publications
(25 reference statements)
6
159
1
10
Order By: Relevance
“…Furthermore, this tumour is usually resistant to conventional chemotherapy and radiation therapy. The pathogenic mechanisms that regulate this aggressive growth behavior of PDC still is to be clarified (Satoh et al, 2001).…”
mentioning
confidence: 99%
“…Furthermore, this tumour is usually resistant to conventional chemotherapy and radiation therapy. The pathogenic mechanisms that regulate this aggressive growth behavior of PDC still is to be clarified (Satoh et al, 2001).…”
mentioning
confidence: 99%
“…[12][13][14][15] Survivin is highly expressed in fetal tissues but is not found in most normal adult tissues. 12 Therefore, the Sur-P should be an excellent candidate for controlling specific expression of therapeutic genes in human tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Furthermore, the level of survivin expression in tumor tissues is correlated with the prognosis of the patients. 15,18,19 These results have provided the rationale of targeting survivin for cancer therapy. For example, downregulation of survivin expression or function induces apoptotic cell death specifically in tumor cells and enhances the antitumor effects of several chemotherapy drugs.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…One family of genes regulated by NFkB are IAPs, acting as suppressors of apoptosis by inhibiting caspase-3, -7 and -9. 9,19 It was suggested that cancer cells, for example, of pancreatic carcinoma, 20,21 can counteract apoptotic signals by the expression of IAPs. We found a pattern of fibrosis-associated enhancement of cIAP1 and survivin protein expression similar to RelA emerge in islets.…”
Section: Discussionmentioning
confidence: 99%